PENINGKATAN PENGETAHUAN SETELAH PENYULUHAN MEDIA MICROSOFT POWERPOINT PENCEGAHAN KARIES EMAIL DENGAN GLASS IONOMOR CEMENT BAHAN FUJI VII - Nike Haryani; Damhuji Damhuji; Rita Herlina (SINERGI : Jurnal Riset Ilmiah, 2026)
The high prevalence of dental caries in Indonesia, especially in children, requires comprehensive prevention efforts. Dental health knowledge is an important factor influencing caries prevention behavior. One early prevention effort is the use of Fuji VII Glass Ionomer Cement (GIC) which has a high fluoride release capacity. This study aims to determine the increase in knowledge of 5th grade students of Elementary School 17 North Pontianak regarding enamel caries prevention using Fuji VII material after being given counseling using Microsoft Powerpoint media. This study is a quantitative study with stages of observation, pre-test, counseling using Microsoft Powerpoint media, and post-test to measure changes in knowledge. The study respondents numbered 74 students. Data analysis used a test of the difference in average knowledge scores before and after the intervention. The majority of respondents were male (55%) with an average age of 10-11 years. The pre-test results showed that the majority of students (72%) had poor knowledge. After the counseling, there was a significant increase where 73% of students were in the good category and there were no more students in the poor category (0%). The average knowledge score increased significantly from 2.99 to 7.55 with a P-value of 0.000 (P < 0.05).